Sustainable supply chain integration in the leather craft industry: A mini systematic literature review - Susanto, Sigit; Santoso, Imam; Astuti, Retno; Wijana, Susinggih (Advances in Food Science, Sustainable Agriculture and Agroindustrial Engineering (AFSSAAE), 2025)
The industry leather craft faced serious sustainability challenges related to water pollution heavy metal contamination and negative environmental, social and economic impacts. This systematic review aimed to fill the research gap on sustainable supply chain integration in the leather craft industry, which was essential to address sustainability challenges and supported industry transformation. The research aimed to identify enabling factors, analyze benefits, formulate implementation strategies, and analyze the impact of sustainable supply chain implementation on stakeholders in the leather craft industry. A systematic review was conducted by searching the Scopus and Web of Science databases using relevant keywords. Inclusion criteria included English-language articles, original research, and a focus on sustainable supply chains in the leather industry. The quality was assessed using the MMAT checklist. The data were extracted using NVivo and synthesized through clustering citations by meaning. Of the 264 articles identified, 36 studies were included in the review. The results showed a range of enabling factors (e.g., regulation, technology, management, and market), benefits (e.g., efficiency, environment, and competitiveness), implementation strategies (e.g., supplier evaluation, technology, and collaboration), and significant impacts on stakeholders (e.g., companies, workers, suppliers, consumers, government, and society). Future research was recommended for multi-stakeholder empirical studies, cross-country comparisons and multidisciplinary approaches.